Water resources implications of integrating malaria control into the operation of an Ethiopian dam - Reis, J.; Culver, T.B.; McCartney, Matthew P.; Lautze, Jonathan F.; Kibret, S. (American Geophysical Union, 2011)
This paper investigates the water resources implications of using a method of hydrological control to reduce malaria around the Koka reservoir in central Ethiopia. This method is based on recent ndings that malaria is transmitted from the shoreline of the Koka reservoir, and on a similar method that was used to control malaria some 80 yr ago in the United States. To assess the feasibility of implementing hydrological control at Koka, we considered the potential impact of the modi ed management regime on the bene ts derived from current uses of the reservoir water (i.e., hydropower, irrigation, ood control, water supply, and downstream environmental ows). We used the HEC-ResSim model to simulate lowering the reservoir by a rate designed to disrupt larval development, which is expected to reduce the abundance of adult mosquito vectors and therefore reduce malaria transmission during the season in which transmission of the disease peaks. A comparison was made of major reservoir uses with and without the malaria control measure. In the 26-yr simulation, application of the malaria control measure increased total average annual electricity generation from 87.6 GWh x y -1 to 92.2 GWh x y -1 (i.e., a 5.3% increase) but resulted in a small decline in rm power generation (i.e., guaranteed at 99.5% reliability) from 4.16 MW to 4.15 MW (i.e., a 0.2% decrease). Application of the malaria control measure did not impact the ability of the reservoir to meet downstream irrigation demand and reduced the number of days of downstream ooding from 28 to 24 d. These results indicate that targeted use of hydrological control for malaria vector management could be undertaken without sacri cing the key bene ts of reservoir operation.